2011
DOI: 10.1002/syn.20942
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the sensitivity of [11C]p943, a novel 5‐HTIB radioligand, to endogenous serotonin release

Abstract: The main objective of the current study was to determine the sensitivity of the PET radioligand [11C]P943 to fenfluramine-induced changes in endogenous 5-HT in nonhuman primate brain. Fenfluramine-induced changes in 5-HT1B occupancy were compared to those obtained by self-block with unlabeled P943. Two baboons and 1 rhesus monkey were given preblocking or displacing doses of fenfluramine (1–5 mg/kg) or preblocking doses of unlabeled P943 (0.2 mg/kg) and imaged with [11C]P943 PET. Receptor occupancy by the low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…We previously demonstrated that the potent serotonin releaser fenfluramine reduced the binding of the 5-HT 1B receptor radioligand [ 11 C]AZ10419369 in non-human primates by up to 50 % (Finnema et al 2010(Finnema et al , 2012, and similar results have been reported by others using the 5-HT 1B receptor radioligand [ 11 C]P943 (Cosgrove et al 2011;Ridler et al 2011) or the 5-HT 1A receptor radioligand [ 11 C]CUMI-101 (Milak et al 2011). The effects of single SSRI doses have also been evaluated in anaesthetized non-human primates (NHPs) in preparation for studies in human.…”
Section: Introductionsupporting
confidence: 76%
“…We previously demonstrated that the potent serotonin releaser fenfluramine reduced the binding of the 5-HT 1B receptor radioligand [ 11 C]AZ10419369 in non-human primates by up to 50 % (Finnema et al 2010(Finnema et al , 2012, and similar results have been reported by others using the 5-HT 1B receptor radioligand [ 11 C]P943 (Cosgrove et al 2011;Ridler et al 2011) or the 5-HT 1A receptor radioligand [ 11 C]CUMI-101 (Milak et al 2011). The effects of single SSRI doses have also been evaluated in anaesthetized non-human primates (NHPs) in preparation for studies in human.…”
Section: Introductionsupporting
confidence: 76%
“…Any possible preexisting differences in CD could be supported by a host of genetic studies in addiction (13, 31) and inherent 5-HT 1B heterogeneity could potentially alter dopamine activity in reward areas by reducing inhibition of GABA release. (30) Potential extracellular 5-HT affects on 5-HT 1B are also an important consideration and given that 5-HT levels were increased in a human post-mortem CD sample (32) and [ 11 C]P943 has been shown to be sensitive to endogenous 5-HT in the nonhuman primate (33), elucidation of this possible affect should be made to further interpretations of 5-HT 1B in CD.…”
Section: Discussionmentioning
confidence: 99%
“…11 C-P943 binding has been shown to be sensitive to changes in 5-HT levels, as well as variation in receptor density (71). One explanation for our results, therefore, is that they reflect a change in the relationship between basal 5-HT and PPI in OCD.…”
Section: Discussionmentioning
confidence: 99%
“…5-HT 1B receptor availability can be assessed in vivo in humans using the PET ligands 11 C-P943 (71-74) and 11 C-AZ10419369 (75). 11 C-P943 has recently been used to document receptor abnormalities in several psychiatric conditions (76-78).…”
Section: Introductionmentioning
confidence: 99%